Integration and Development in Schizotypy Research: An Introduction to the Special Supplement - Debbané, Martin (Schizophr Bull, 2015)
In its fifth decade of existence, the construct of schizotypy is recapturing the early scientific interest it attracted when Paul E. Meehl (1920–2003), who coined the term, pioneered the field of schizotypy research. The International Lemanic Workshop on Schizotypy, hosted at the University of Geneva in December 2013, recently offered an opportunity to address some of the fundamental questions in contemporary schizotypy research and situate the construct in the greater scheme of future scientific projects on schizophrenia and psychological health research. What kind of knowledge has schizotypy research provided in furthering our understanding of schizophrenia? What types of questions can schizotypy research tackle, and which are the conceptual and methodological frameworks to address them? How will schizotypy research contribute to future scientific endeavors? The International Lemanic Workshop brought together leading experts in the field around the tasks of articulating the essential findings in schizotypy research, as well as providing some key insights and guidance to face scientific challenges of the future. The current supplement contains 8 position articles, 4 research articles, and 1 invited commentary that outline the state of the art in schizotypy research today.